Depiction of the story of Chandakaushika Nag and Mahavir - Temples of India Project Team (Jio Institute, 2024)
The painting in the inner/upper circle in the ceiling of the mandapa (pillared hall) likely depicts the story of Chandakaushika Nag and Mahavir. According to the tale, as Mahavir travelled through a forest, a snake named Chandak blocked his path. However, Mahavir instead of being scared of him stood at the place firmly. Chandak bit the Tirthankara, yet the latter remained calm, intending no harm to the snake. This story intends to teach everyone the importance of controlling anger and cultivating compassion. Mahavir has a divine halo behind his head, painted in golden colour. A temple dedicated to the snake is shown at the background of the painting. The inscription from this painting is not entirely legible, but it certainly includes the name of Mahavir Swami.